2015
DOI: 10.31586/management.0202.01
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Role of Personality Factors in Organizational Citizenship Behaviors

Abstract: Organizational citizenship behavior (OCB) as a non-mandatory cooperation with others significantly influences an organization's performance and social capital. In this paper it has been attempted to study the role of personality traits based on the Big Five model namely, extraversion, agreeableness, conscientiousness, openness to experience and neuroticism in the performing of organizational citizenship behavior, while Altruism, civic virtue, organizational conscientiousness, courtesy and sportsmanship were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…For example, in a study conducted in the banking sector, there was a significant positive relationship between conscientiousness, compliance and self-discipline personality traits and OCB. However, there was a negative relationship between neurotic personality traits and OCB, and this negative relationship caused the employee to experience organisational problems (Saeedy and Rastgar, 2015). A similar result was demonstrated in a study conducted with a sample of physicians, and it was found that four personality factors except neuroticism were positively correlated with OCB (Kumar et al, 2009: p.73).…”
Section: The Role Of Personality In the Relationship Between Psychological Contract And Organisational Citizenship Behaviourmentioning
confidence: 57%
“…For example, in a study conducted in the banking sector, there was a significant positive relationship between conscientiousness, compliance and self-discipline personality traits and OCB. However, there was a negative relationship between neurotic personality traits and OCB, and this negative relationship caused the employee to experience organisational problems (Saeedy and Rastgar, 2015). A similar result was demonstrated in a study conducted with a sample of physicians, and it was found that four personality factors except neuroticism were positively correlated with OCB (Kumar et al, 2009: p.73).…”
Section: The Role Of Personality In the Relationship Between Psychological Contract And Organisational Citizenship Behaviourmentioning
confidence: 57%
“…Simply put, organizational citizenship behavior can be in the form of employees who help solve the problems of others who are outside the authority and responsibilities of their jobs, senior employees who have experience providing training to new employees outside working hours, or employees who actively participate in team meetings when discussing improvements or housekeeping at work. Saeedy (2015) states that personality can also be one of the predictors in evaluating how much OCB is done by employees to be able to retain the best employees owned by the organization. So it is important for organizations to know the personality of each employee.…”
Section: Introductionmentioning
confidence: 99%